Regulation of Glial Cell Functions by PPAR-γ Natural and Synthetic Agonists. (17th March 2008) - Bernardo, Antonietta; Minghetti, Luisa
Abstract : In the recent years, the peroxisome proliferator-activated receptor-γ (PPAR-γ ), a well known target for type II diabetes treatment, has received an increasing attention for its therapeutic potential in inflammatory and degenerative brain disorders. PPAR-γ agonists, which include naturally occurring compounds (such as long chain fatty acids and the cyclopentenone prostaglandin 15-deoxyΔ 12, 14 prostaglandinJ 2 ), and synthetic agonists (among which the thiazolidinediones and few nonsteroidal anti-inflammatory drugs) have shown anti-inflammatory and protective effects in several experimental models of Alzheimer's and Parkinson's diseases, amyotrophic lateral sclerosis, multiple sclerosis and stroke, as well as in few clinical studies. The pleiotropic effects of PPAR-γ agonists are likely to be mediated by several mechanisms involving anti-inflammatory activities on peripheral immune cells (macrophages and lymphocytes), as well as direct effects on neural cells including cerebral vascular endothelial cells, neurons, and glia. In the present article, we will review the recent findings supporting a major role for PPAR-γ agonists in controlling neuroinflammation and neurodegeneration through their activities on glial cells, with a particular emphasis on microglial cells as major macrophage population of the brain parenchyma and main actors in brain inflammation.